Library services from birth to five delivering the best start (Facet Publishing, 2015)
Following on from their ground-breaking first book. Delivering the first start, Rankin and Brock return to the subject of pre-school and early years library provision with contributions and case studies from innovators and experts around the world. There is a growing awareness of the significance of the first five years of life for intellectual, social and emotional development and early intervention is of political interest. This book provides knowledge and understanding about early language and literacy development and how young children become successful through enjoyable and meaningful experiences.